SOSYAL MEDYA PLATFORMLARINDA YAYGINLAŞAN SÖZDİZİMSEL EKSİLTİLER ÜZERİNE. - SARI, İsa (Turkbilig/Turkoloji Arastirmalari Dergisi, 2026)
In digital platforms, which offer instant multimedia communication and interaction, various unusual new structures emerge independently of the codified paPerns and structures of language, and these structures are adopted and accepted by users, becoming widespread. Especially on social media that offer uncontrolled, instant communication and sharing opportunities, users quickly adapt to such new structures that can be called "fashionable", and these structures are adopted and used by different user groups over time. These structures may be preferred by more people for a number of underlying social, psychological or techno-cultural reasons such as being accepted in a certain community or medium, being similar to other users, interaction and appreciation. In this context, it is observed that a number of structures that lack a clear predicate, present the appearance of a simple elliptical structure, but are understandable and analyzable only within their own sharing context, and can be supported by emojis from time to time, have become widespread in social media, especially in the last few years. In this study, ellipsis constructions, which are usually associated with a shared visual, video or similar contextual material and do not convey any information/judgment without this material, were analyzed around sample representation data through platforms like X, Instagram or Youtube, and their formation characteristics were determined. The findings show that such constructions are not simple grammatical omissions, that they are a new form of expression required by multimodal communication and that they have different sub-types. In addition, it has been determined that there are different sub-purposes and motivations such as the principle of economy, linguistic creativity, fulfilling emotional, humorous or social functions, and increasing interaction in the formation and prevalence of such constructions.